Diagnosis of the supply system of agricultural products in a Colombian population - Herrera Ochoa, Óscar Javier; Hualpa, Andrés Mauricio; Luna, María Sofía (Ingeniería Solidaria, 2023)
Introduction: The article is the product of phase 1 of the research: "Management Model for the Sustainable Supply of Fruits and Vegetables in shopkeepers of the municipality of Mosquera through an Associativity scheme", carried out at the University of La Salle in the 2021.Problem: The food supply in Mosquera is disjointed, being carried out independently by each shopkeeper, thus generating cost overruns, especially in transportation.Objective: Characterize and diagnose the food supply system in Mosquera.Method: Analysis of the unit of analysis by collecting information by direct observation and through guided interviews, carrying out a descriptive correlational analysis for the analysis of the variables based on the characterization of the system.Results: Establishment of key factors and variables of the food supply system in Mosquera such as location, number of products by type, purchase frequency, storage and display methods, among others. In addition, the diagnosis of the strategic, tactical and operational level through the use of organizational and engineering analysis techniques.Conclusions: Strategies to improve the supply chain as a whole from the economic, environmental and social spheres of Mosquera, which take into account the efficient and sustainable operation of the system through a scheme of associativity of the shopkeepers in the municipality. This can contribute to food security through greater access to food with reduced prices and timely availability in the localities under study.Originality: Structuring of factors and operationalization of variables to define the complete food supply operation.Limitations: Particular conditions of use for the practical object of study.
Keywords: supply; supply chain; strategic and operational diagnosis; logistics; shopkeepers